The implementation of the list of exceptions of article 5 of the Information Society Directive 2001/29/EC in selected Member States - von Lewinski, Silke (Revista Pe.i., 2011)
Article 5 of the Information Society Directive first needs to be put into context with other directives that contain exceptions to protection and with the tools for legal harmonization in general. Also the system of Article 5, which is quite long, is recalled, before provisions on exceptions in national laws of selected Members States before and after harmonization are dealt with. Within the scope of this presentation, only a presentation of the main legal traditions of, and an overview of implementation of Article 5 in, France, Germany, and the United Kingdom are possible; the three-step test is not included in this presentation, since Professor lucas has separately dealt with that topic. Finally, a number of ideas to modify the existing system of exceptions under Article 5 of the Information Society Directive as recently expressed by a number of lobbyists and academics will be briefly presented and discussed.